2021
DOI: 10.3389/fmed.2021.724283
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvasculature and Conjunctival Vessel Alterations in Patients With Systemic Lupus Erythematosus—An Optical Coherence Tomography Angiography Study

Abstract: Purpose: To evaluate the conjunctival and fundus retinal vessel density in patients with systemic lupus erythematosus (SLE) with optical coherence tomography angiography (OCTA), and to investigate the relationship between vessel density and clinical indicators.Methods: Twelve patients with SLE (24 eyes) and 12 healthy controls (24 eyes) were recruited. OCTA was used to examine the superficial retina layer (SRL) and deep retina layer (DRL) in the macular retina and conjunctival capillary plexus of each eye. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
(41 reference statements)
0
12
2
Order By: Relevance
“…It has been reported that retinopathy may be more common in patients with active inflammation. 20 No correlation between SLEDAI and retinal VD was found in the studies of Arfeen et al and Shi et al 14,21 We did not find this correlation in our study either. However, most of the patients included in the abovementioned studies were in the inactive or low-activity phase.…”
Section: Discussioncontrasting
confidence: 67%
“…It has been reported that retinopathy may be more common in patients with active inflammation. 20 No correlation between SLEDAI and retinal VD was found in the studies of Arfeen et al and Shi et al 14,21 We did not find this correlation in our study either. However, most of the patients included in the abovementioned studies were in the inactive or low-activity phase.…”
Section: Discussioncontrasting
confidence: 67%
“…Our data support the utility of the OCT-A as a non-invasive tool to the early detection of retinal vascular abnormalities in AAV patients in whom both the cardiovascular and the complement-mediated in ammation might lead to retinal damages [51][52][53]. As reported from evidence in the literature, signi cant correlations occur between OCT-A abnormalities and disease activity in systemic autoimmune diseases as SLE suggesting that retinal capillary plexi may represent the "sentinel" of the microvascular network involved in systemic in ammatory disorders [29][30][31][32][33]. Accordingly, we documented in our AAV cohort that disease damage resulted directly related with the BVAS-disease activity as well as the disease duration: interestingly, vessel density from AAV patients resulted negatively related with disease-related damage (assessed by VDI) suggesting that a higher disease activity a greater microvascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature supports the role of the optical coherence tomography angiography (OCT-A) as a non-invasive diagnostic tool for the early detection of subclinical retinopathy in systemic autoimmune diseases: accordingly, we recently documented, for the rst time, subclinical abnormalities in retinal microvascular network in patients with Systemic Lupus Erythematosus (SLE) by using OCT-A [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 91%
“…OCTA is a noninvasive, accessible, and relatively inexpensive method for monitoring macular blood ow. Previous studies have shown changes in macular blood ow in patients with hypertension, chronic kidney disease, hemodialysis, diabetes, and in ammatory diseases [2][3][4].…”
Section: Introductionmentioning
confidence: 98%